Characteristics healthy ageing among the elderly in Southern Thailand - Somporn Rattanapun (2018)
A descriptive research was used to study the characteristics of healthy ageing which was created based on Rowe and Khan's Model which included; avoiding disease and disability, maintaining high cognitive and physical function, and active engagement with life. The subjects consisted of 370 elderly people who resided in Thasala sub-district, Thasala district, Nakhon Si Thammarat province who were recruited by the probability proportion to the size and simple random sampling. Data were collected by using the Elderly Health Questionnaire which was developed by the researcher. Data were collected over the period January to May 2006 and analyzed by using frequencies and mean score. The reliability coefficient of this questionnaire was 0.87 and the value of CVI was 0.91. The findings revealed that the mean scores of the overall healthy ageing and maintaining high cognitive and physical function were at a high level. Although the mean scores of avoiding disease and disability was at a moderate level due to the subjects still had limited some daily living practices namely having stretching and aerobic exercise, avoiding fat diet and fried diet, drinking milk or soy milk, avoiding taking alcohol, consulting health personnel, and having regular physical check-up. Active engagement with life was also at a moderate level due to the subjects still had limited manifested participating in elderly club and community activities. Thus, to enhance the healthy ageing, health care providers should design program interventions by motivating and promoting these daily living practices.